Functional Properties of Sago Grub Protein Concentrates With Different Initial Drying Methods - Tuhumury, Helen C D; Picauly, Priscillia (AGRITEKNO: Jurnal Teknologi Pertanian, 2023)
The objective of this study was to determine the effects of various initial drying methods on the functional properties of sago grub protein concentrates and characterize their functional properties. In this work, a block randomized design was employed to extract sago grub protein concentration using cabinet dryer, sun, and oven drying methods. The variables observed were the foaming capacity, foaming stability, water holding capacity, and fat absorption capacity of the protein concentrate. Results showed that different initial drying methods of sago grub did not affect the foaming capacity, foaming stability, or fat absorption capacity of the resulting protein concentrates. In contrast, the water holding capacity of the protein concentrates was significantly affected by different initial drying methods on sago grub. Various initial drying methods resulted in the protein concentrates having a foaming capacity of 7.5–12.5%, a foaming stability of 3.5-7.5%, a water holding capacity of 1.9–2.35 mL/g, and a fat absorption capacity of 299.12–306.75%.